2019
DOI: 10.1111/1753-0407.12907
|View full text |Cite
|
Sign up to set email alerts
|

Tapering decay of β‐cell function in Chinese patients with autoimmune type 1 diabetes: A four‐year prospective study

Abstract: Background This study investigated the natural progression of β‐cell function in Chinese autoimmune type 1 diabetic (T1D) patients and clarified factors possibly influencing the course of the disease. Methods The natural progression of β‐cell function of 325 newly diagnosed Chinese autoimmune T1D patients was assessed by fasting and postprandial C‐peptide (FCP and PCP, respectively) levels. β‐Cell function failure was defined as FCP <50 pM and PCP <100 pM, whereas preserved β‐cell function was defined as FCP >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…With respect to beta-cell function evaluation, FCP and 2hCP are frequently used in clinical practice due to their good consistency with MMTT or glucagon stimulated C-P [33][34][35][36] and the ability to predict beta-cell function in autoimmune T1DM 37,38 . In the landmark Diabetes Control and Complications Trial (DCCT) study, the role of beta-cell function was first demonstrated in T1DM patients using intensive insulin therapy 39 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to beta-cell function evaluation, FCP and 2hCP are frequently used in clinical practice due to their good consistency with MMTT or glucagon stimulated C-P [33][34][35][36] and the ability to predict beta-cell function in autoimmune T1DM 37,38 . In the landmark Diabetes Control and Complications Trial (DCCT) study, the role of beta-cell function was first demonstrated in T1DM patients using intensive insulin therapy 39 .…”
Section: Discussionmentioning
confidence: 99%
“…after MMTT are commonly used indicators to assess pancreatic β-cell function. 34,35 The role of β-cell function in T1D patients treated with intensive insulin therapy was initially demonstrated in the DCCT. 36 Patients with CP between 200 and 500 pmol/L after MMTT had lower HbA1c levels, daily insulin dosage, and incidence of severe hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…2hCP following MMTT stimulation can reflect endogenous insulin secretion since MMTT comprises carbohydrates, fats, and proteins that promote insulin secretion under near‐physiological settings. Thus, FCP and 2hCP after MMTT are commonly used indicators to assess pancreatic β ‐cell function 34,35 . The role of β ‐cell function in T1D patients treated with intensive insulin therapy was initially demonstrated in the DCCT 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Islet β‐cell function was assessed using fasting C‐peptide (FCP) and 2‐h postprandial C‐peptide (PCP) values. For autoimmune type 1 diabetes mellitus, FCP ≥200 pmol/L or PCP ≥400 pmol/L showed preserved β‐cell function 30 . The FCP cutoff value of ≥200 pmol/L was also applied to define adequate β‐cell function in previous studies of type 2 diabetes mellitus 31 .…”
Section: Methodsmentioning
confidence: 99%